IMPACT OF INTERNAL CONTROL IN REDUCING THE COSTS OF NON-CONFORMITY WITH QUALITY STANDARDS - Hazim Abed Azeez (Scholar Express Journals, 2022)
The study sheds light on internal control as an independent variable and the elements of quality costs in their dimensions (preventive costs, evaluation costs, internal failure costs, external failure costs) as a dependent change. This is to find out the impact of internal control in reducing the costs of nonconformity with quality standards in Ur General Company for Engineering Industries. In order to achieve the aim of the research, (40) questionnaires were distributed to a randomly selected sample of workers in Ur Company. Then, a descriptive-analytical method was adopted to test the research hypotheses. Likewise, the statistical package for social sciences (SPSS), including its measures (arithmetic mean, standard deviation, Spearman correlation coefficient, a Beta coefficient to measure the impact), was also adopted in the study. After the results appeared, the hypotheses tested, and the research problem interpreted, several conclusions were reached, the most important of which is. that the company suffers from inefficient use of sound accounting methods in measuring quality costs and reducing them and then weaknesses in internal control elements; in addition to the insufficient knowledge of the concept of quality costs and its components by the employees in the Accounts and Quality Departments and even senior management. Similarly, the company's members lack straightforward training programs, as the training sessions were restricted to a specific category for their promotions according to the job grading scale
Keywords: Internal Control; Costs of Non-Conformity; Quality costs; Prevention costs